1985
DOI: 10.1097/00004032-198511000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Radionuclides in Foods, 1978–1982

Abstract: Samples from the U.S. Food and Drug Administration's total-diet, market-basket program, samples of imported foods, and samples collected near nuclear power plants were analyzed for radionuclides. Most radionuclides were below the limit of detection for a majority of the samples; however, data are reported for 3H, 90Sr and 137Cs in certain samples. Generally a downward trend is observed for 90Sr when data for the 5-yr period were compared. The total dietary intake of either 90Sr or 137Cs is well within Range I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This resulted in a variety of studies of the dietary intake of key fallout nuclides such as 137 Cs and 90 Sr found in food products (Cunningham et al, 1989;Simpson et al, 1981;Stroube et al, 1985;United States Atomic Energy Commission, 1963). The high levels of contamination documented between 1957 and 1964 were not reached again until the Chernobyl nuclear plant accident of April 1986 (Cunningham and Anderson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in a variety of studies of the dietary intake of key fallout nuclides such as 137 Cs and 90 Sr found in food products (Cunningham et al, 1989;Simpson et al, 1981;Stroube et al, 1985;United States Atomic Energy Commission, 1963). The high levels of contamination documented between 1957 and 1964 were not reached again until the Chernobyl nuclear plant accident of April 1986 (Cunningham and Anderson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2.3) on irradiation with epithermal neutrons, in so-called epithermal neutron activation analysis (ENAA), nowadays more often called epithermal instrumental neutron activation analysis (EINAA). For this reason, EINAA has been used extensively for iodine determination in foodstuffs since the beginning of the eighties until now (Fardy and Mcorist, 1984;Stroube and Lutz, 1985;Stroube et al, 1987;Rao et al, 1995;Hou et al, 1997a, b;Nichols et al, 1998;Kucera et al, 2004;Akhter et al, 2004;El-Ghawi and Al-Sadeq, 2006). In such conditions, iodine is activated more selectively (together with other nuclides with high resonance integrals), because the high background activities from the elements Na, K, and Cl whose radioisotopes are formed according to the "1/v" law (v -velocity of neutrons) are suppressed.…”
Section: Neutron Activation Analysis and Other Nuclear Analytical Tecmentioning
confidence: 99%
“…Dosimetry methods used are based on the concepts of ICRP 30 (1979), as implemented using the CINDY computer code Stroube, Jeline, and Baratta (1985). The concentration in milk may run from 0.04 to 0.2 Bq/l.…”
Section: Strontiummentioning
confidence: 99%